Pendidikan Kesehatan Prokes Masa Covid-19 Varian Baru Pada Kelompok Pengajian di Dusun Kepel, Lojejer, Wuluhan - Asmuji Asmuji; Dwi Yunita Haryanti; Annisa Eka Adhitya Wardani (Indonesian Journal Publisher, 2023)
The purpose of this service is to increase partners' knowledge and awareness in recognizing and preventing the spread of the new variant of Covid-19. Until now, Covid-19 has undergone several mutations. For the latter is the emergence of the Arcturus variant. Covid-19 cases have also continued to increase since they were first discovered in Indonesia, although they are not as violent as before. This condition makes partners neglect to take care of themselves so they don't get infected. Because you feel safe, you don't need to worry anymore. This phenomenon is a problem that must be addressed immediately, because the Covid-19 case, which is currently in a sloping period and has experienced a very significant decline, is no guarantee that it will be safe from the emergence of new variants and their transmission. The new variant of Covid-19 cases in Mitra has not been detected at this time. However, cases of coughs, colds and fever in partners are still common. For this reason, to prevent Partner negligence which can be fatal, it is necessary to conduct health education for Partners. Health counseling to partners was held on Saturday, 13 May 2023 which was attended by 19 people. This activity was carried out by two lecturers and two students from the Faculty of Health Sciences, Muhammadiyah University of Jember. The results of health education show an increase in knowledge about the new variant of Covid-19 Arcturus, both understanding, causes, signs and symptoms, prevention and treatment. Before counseling 89% of partners had insufficient knowledge, and after counseling 79% of partners had good knowledge about Covid-19. In addition, partners are taught the 7 steps to wash their hands properly. And partners are able to practice it sequentially correctly.